Exploring teachers' perspectives on career development: Q methodology research. (February 2023) - Chaaban, Youmen; Alkhateeb, Hadeel; Abu-Tineh, Abdullah; Romanowski, Michael
Abstract: Recruiting, preparing and supporting teachers remain a public concern in many countries, with similar concerns voiced in Qatar. Using a Systems Theory Framework, this study explored the systems of influence on Qatari teachers' career development within individual, social, and environmental-societal contexts. Q methodology was applied, using a 40-statement Q-sample. Forty-two teachers participated in this study, including 27 males and 15 females. Results revealed four distinct perspectives with minimal consensus, and alluding to different career plans: (F-1) considering career prospects, (F-2) pursuing leadership positions, (F-3) surviving in the profession, and (F-4) contemplating leaving the profession. Implications for policy planning are discussed.